Existence of Stationary Solutions for some Systems of Integro-Differential Equations - Vougalter, Vitali; Volpert, Vitaly (Discontinuity, Nonlinearity, and Complexity, 2026)
The article deals with the existence of solutions of a system of nonlocal reaction-diffusion equations which appears in population dynamics. The proof relies on a fixed point technique. Solvability conditions for elliptic operators in unbounded domains which fail to satisfy the Fredholm property are being used.